The light between us : stories from heaven, lessons for the living - Jackson, Laura Lynne (Spiegel & Grau, 2015)
"The Light Between Us provides guideposts for living a rich and fulfilling life. In her beautiful worldview, Laura Lynne Jackson reminds us that our relationship to those we love endures across space and time; that we are all connected and invested in one another's lives; and that we are here to give and receive love selflessly. Her story offers a new understanding of the vast reach of our consciousness and enlarges our view of the human experience,"--Amazon.com.